Bilateral Outpatient Total Knee Arthroplasty – Is it Feasible, Safe, and Worth Considering: A Pilot Study - Sunil Rajan; Saurabh Jain; Chetan Singh Dhosariya; Ashish Goyal (Journal of Orthopedics, Traumatology and Rehabilitation, 2023)
Introduction: Outpatient total knee arthroplasty (TKA) in selected patients has proved to be beneficial to both patients and health-care systems in terms of safety, reoperations, readmission rate, complications, cost-effectiveness, increased patient satisfaction, and improved outcome scores. However, these benefits of outpatient TKA have been limited to unilateral TKA. Hence, we reviewed the results of bilateral outpatient TKA in five patients to educate surgeons about the feasibility, safety, benefit, and area of research for bilateral outpatient TKA and its worth consideration in selected groups of patients to decrease patient morbidity and cost. Materials and Methods: Five bilateral knee arthroplasties done as outpatient surgeries at our center were reviewed for patient satisfaction, readmission, reoperation, emergency visit without readmission, unplanned clinic visits, and complications. All these cases followed proper selection criteria, adequate preoperative planning, and strict adherence to our standard operating protocols. Results: Five patients of bilateral outpatient TKA with a mean age of 48.6 years were included in the study. All patients have excellent outcomes at 1-month follow-up. The mean Knee Society Score was 91. None of the patients required reoperation or revision surgery. All the patients demonstrated a high level of satisfaction, without any complications of instability, infection, ileus, urinary tract infection, or deep vein thrombosis. Conclusion: Bilateral outpatient TKA can be considered a suitable alternative with benefits of reduced hospital stay, and hence decreased morbidity and cost, early mobilization and recovery, economical advantages, minimal pain owing to multimodal analgesia, faster return to normalcy, and less mental stress or disturbances, but in selected patients at specialized center only. The study stresses on the fact of bilateral outpatient TKA should also considered a key area of research in the field of outpatient TKA in addition to other areas of universal selection criteria, ideal risk assessment tool, safety aspect, surgical duration, ambulation, and reasons for not able to discharge.